Are Indications For Esophago Gastro Duodenoscopy Properly Followed? - Sultan, saad H; Al- Atroshi, Mohammed A; Kamal, Zuhair B; Hussein, Wissam A (AL-Kindy College Medical Journal, 2011)
Background: Symptoms related to the upper gastro-intestinal tract are very common. Attribution of these symptoms to upper G. I. T.diseases are usually done on clinical bases, which could be confirmed by Esophago Gastro Duodenoscopy (EGD). The use of such tools might increase the diagnosis accuracy for such complaints. The indications for upper G I endoscopy might decrease the negative results of endoscopies.Objective: To follow strict indications for Esophago Gastro Duodenoscopy in order to decrease the negative endoscopy results. Methods: One thousand eight hundred and ninety cases were subjected to EGD from Feb. 1999 to Feb 2009 at Alkindy Teaching Hospital and Abd-Al-Majeed private hospital in Baghdad, Iraq. A special endoscopy unit form was prepared containing data from patients, clinical complaint, indications for endoscopy request, and the endoscopic diagnosis, biopsies were taken when indicated and subjected to histopathological examination. All these data were studied and analyzed.Results: Out of the total 1890 patients there were 1114 males and 776 females with male to female ratio 3/2, the most common age group ranged from 21 to 50 years with a mean age of 32 years. Upper abdominal pain was the most common indication (30%), upper GI bleeding (27.94%), duodenal ulcer follow up (25.5%). The diagnosis of chronic DU was established in (40.21%) of cases, normal endoscopic results were found in (34.6%), duodenitis and gastritis in (15.2%).Conclusion: The high number of normal gastrointestinal endoscopies necessitates the need to follow strict indications before subjecting the patients for endoscopy.